Technical and economic feasibility of solar powered air conditioners in Brunei Darussalam - Alhakmi, E; Khalil, Ashraf; Abdul Hamid, Zanidi; Peng, Ang Swee; Uddin, M. R.; Jaafar, Saifulbahri; Mohammed, I.; Khan, Sheroz; Yaacob, Mashkuri (Mattingley Publishing, 2019)
On daily basis, a huge amount of fossil fuel is being burnt which results in a substantial amount of greenhouse gasses being released into the atmosphere. Air conditioners are becoming more common and are a major strain on energy demands especially in tropical climate countries like Brunei Darussalam. The photovoltaic electricity is a clean and sustainable. In this paper, we present a techno-economic feasibility study for solar powered air conditioning system in Brunei Darussalam. Four alternatives are investigated, 1) the PV system supplies 50% of the loads, 2) the PV system supplies 75% of the loads, 3) the PV system supplies 100% of the loads, and finally 4) the PV system supplies 125% of the loads. Where in the last two case the excess electricity is sold to the grid. With 0.3$ feed-in tariff. The best alternative is the grid-connected PV system with 125% capacity factor which was chosen due to its short payback time period as well as high profit rate over the lifetime of the project.